Просторовий розподіл потенціалу техногенних навантажень на території Луцької урбоекосистеми - Фесюк, Василь Олександрович; Мороз, Ірина Анатоліївна; Fesiuk, Vasyl O.; Moroz, Iryna A. (Луцький національний технічний університет, 2015)
Основним завданням статті є визначення структури потенціалу техногенних навантажень, оцінка масштабів його складових і аналіз просторового розподілу по території м. Луцька. Результати роботи: розглянуто теоретико-методологічні засади районування території міст за потенціалом техногенних навантажень; оцінено і картографовано щільність викидів забруднюючих речовин підприємствами м. Луцька, утворення відходів по промислових підприємствах, хімічної та вибухо-пожежної небезпеки території, а також середній модуль навантаження на природне довкілля м. Луцька.

Analysis of the spatial distribution of potential technogenic loads on the territory of cities is an important part of assessing the ecological safety of the city territory. It allows you to identify areas of highest severity of the ecological situation. The main task of the article is to identify potential technogenic structure loadings assessment of the extent of its components and analysis of spatial distribution on the territory of Lutsk. In this paper used the methods of mathematical modeling (for model building ecological safety of the sities) and methods of electronic cartography (for constructing the corresponding maps). Results of the work: The theoretical and methodological foundations of zoning the territory of cities after potential of the technogenic loading are considered. It is appraised and it is drawn a map of closeness of the troop landing of contaminating matters by the enterprises of Lutsk, formation of wastes on industrial enterprises, chemical and explosive-fire danger of territory, and also middle module of loading on surrounding the natural environment of Lutsk. As a result of the imposition of a constructive and geographical analysis layers obtained models, we built a synthetic medium mapped schemes territorial distribution module anthropogenic impact on the natural environment m. Lutsk. As seen from kartoshemy highest potential anthropogenic impact (anthropogenic load module) for the city are within industrial zones. This is particularly clear within the city. Lutsk, where the three largest (southern, south-eastern and north-eastern) from four industrial zones of objective clearly drawn in the relief field distribution module anthropogenic influence.
Spatial distribution of technogenic potential on territories of Lutsk urboecosystem
Keywords: ecological safety; tehnogenic loading; ddle module of loading on surrounding the natural environment of cities; екологічна безпека; техногенні навантаження; середній модуль навантаження на природне довкілля міст